The Association Between Neonatal Respiratory Distress Syndrome and Plasma IgG N-Glycosylation: A Case-Control Study - Wang Y; Shen Q; Yan R; Wang M; Xu M; Chen H; Li D (Journal of Inflammation Research)
Yingjie Wang,1,2,* Qingqing Shen,3,* Ruxu Yan,1,2 Meng Wang,2,4 Min Xu,5 Hanxiang Chen,1 Dong Li2,6 1Department of Clinical Laboratory Medicine, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Shandong Medicine and Health Key Laboratory of Laboratory Medicine, Jinan, Shandong, People’s Republic of China; 2School of Public Health and Health Management, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China; 3Department of Neonatology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Shandong, People’s Republic of China; 4Jinshan District Center for Disease Control and Prevention, Shanghai, People’s Republic of China; 5Department of neonatology, Tai’an Maternal and Child Health Hospital, Tai’an, Shandong, People’s Republic of China; 6Jining Medical University, Jining, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hanxiang Chen, Email hxchen@sdfmu.edu.cn Dong Li, Email jnmcdongli@163.comBackground: Neonatal respiratory distress syndrome (NRDS) is the leading cause of neonatal death. Changes in plasma immunoglobulin G (IgG) N-glycosylation have been demonstrated in a variety of diseases. However, its implications and clinical significance in NRDS remain to be clarified.Methods: To determine the effect of IgG N-glycosylation on NRDS, we recruited 88 NRDS participants and 120 control participants from December 2021 to September 2022. Plasma was collected, IgG was isolated and purified, and the glycogram was analyzed by ultra performance liquid chromatography (UPLC) with fluorescence detector.Results: The occurrence of premature rupture of membranes (PROM) [OR=9.043(1.036– 78.966), P=0.046] and the elevation of γ-glutamyltransferase (GGT) [OR=1.015(1.001– 1.029), P=0.032] were independent risk factors for the occurrence of NRDS. Furthermore, the area percentages of GP1, GP3, GP4, GP11, GP13, and GP24 were significantly higher in NRDS patients compared with control group. Conversely, GP14 was observed to be significantly lower. Furthermore, an increase in plasma IgG sialylation and core fucosylation was observed in NRDS, whereas the modification with galactosylation was decreased. The model constructed using GP1, GP13, GP14, PROM, and GGT as composite indices demonstrated robust predictive performance (AUC=0.902, 95% CI: 0.851– 0.953).Conclusion: Patients with NRDS frequently exhibit alterations in the glycosylation of plasma IgG. These findings provide new insights into the diagnosis of NRDS and clinical treatment.Keywords: neonatal respiratory distress syndrome, IgG N-glycosylation, ultra performance liquid chromatography, premature rupture of membranes